The influence of the disclosure of diabetes on the cognitive, physical ability and diabetes self‐management in diabetic employed adults in Saudi Arabia. Issue 2 (10th December 2021) - Alshutwi, Sitah; Miligi, Eman; Alhumidan, Lujain; Almutairi, Adel F.
Abstract: Background: Diabetes is a serious medical condition that may cause blindness, renal failure and amputation of the lower limbs, stroke and myocardial infarction. The global incidence of diabetes increases continuously. The self‐management of diabetes can be problematic and burdensome, especially if employed individuals choose not to reveal their illness. The workplace has been highlighted as an important element that may impact how employed individuals, diagnosed with diabetes and managed their illness. Aim: To describe the influence of diabetes disclosure on the cognitive, physical ability and diabetes self‐management of employed adults with diabetes in Saudi Arabia. Design: A descriptive correlational study. Methods: This study used a self‐administered questionnaire, including the Checklist Individual Strength and Perceived Diabetes Self‐Management Scale, for data collection. The sample size was 250 employed adults with diabetes. The data were analysed using descriptive statistics, Spearman's correlation coefficient and bivariate analysis. Results: A significant correlation was found between diabetes self‐management and support from co‐workers ( r = .55, p < .05), and the employees who received more support from their co‐workers were able to perform diabetes self‐management. The results also indicate that employees who received support at their workplace reported improved concentration, motivation and activity ( r = .41, p < .05). Conclusion: It is essential for top management and policymakers to implement supportive programmes in the workplace, and considering a constant, not rotating, work schedule.